2014
DOI: 10.1007/s11695-014-1180-7
|View full text |Cite
|
Sign up to set email alerts
|

Greater Weight Loss with the Omega Loop Bypass Compared to the Roux-en-Y Gastric Bypass: a Comparative Study

Abstract: In this short-term study, we observed a greater weight loss with OLB and similar efficiency on metabolic control compared to RYGBP. Long-term evaluation is necessary to confirm these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 25 publications
4
41
0
Order By: Relevance
“…After performing various bariatric operations, the author was trained in the LMGBP by Dr. Rutledge and has been conferring with the other LMGBP surgeons worldwide, especially at the annual Paris LMGB Consensus Conferences. Papers have been published showing superiority of the LMGBP to the Roux-en-Y gastric bypass (RYGBP) and the sleeve gastrectomy (SG) [23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…After performing various bariatric operations, the author was trained in the LMGBP by Dr. Rutledge and has been conferring with the other LMGBP surgeons worldwide, especially at the annual Paris LMGB Consensus Conferences. Papers have been published showing superiority of the LMGBP to the Roux-en-Y gastric bypass (RYGBP) and the sleeve gastrectomy (SG) [23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…First, the number of patients included in our study was too low to achieve a powerful statistical analysis. Second, as already shown in previous studies [10,11,29], MGB is technically less challenging than RYGB even when dealing with unfavorable patients' body habitus and/or after revisional surgery. …”
Section: Discussionmentioning
confidence: 63%
“…In several studies MGB has shown to be a safe option for treatment of obese patients and easier when compared to other malabsorptive procedures [10,[26][27][28][29]. Furthermore, in a prospective randomized controlled clinical trial, MGB was shown to be as effective as the standard RYGB [9].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have documented more durable weight loss after the MGB [3,13,22,[52][53][54][55]. Also, better quality of life has been found after MGB [56,57].…”
Section: Comparison With Other Bariatric Operationsmentioning
confidence: 98%